2020
DOI: 10.3390/jfb11030052
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Nickelide in Midface Fractures Treatment

Abstract: Background: The question of reconstruction of human tissues and organs with the use of medical materials is still open, because of the accurate requirements for their biological and physical features. The aim of this study was to prove the efficiency of titanium nickelide constructors in treatment of isolated orbital floor fractures or combination with zygomatico-orbital complex fractures. Methods: Patients with a fracture of zygomatico-orbital complex and/or low orbital floor (n = 44) carried out different tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…With additional research, nitinol was found to have distinctive properties such as unique memory of geometric shapes, superelasticity, high strength, resistance to rust, non-magnetic properties, wear resistance, and fatigue resistance ( 20 ). Due to its non-toxic resistance to human medium corrosion and good cell adhesion, nitinol is widely used in orthopedics ( 21 ), gastrointestinal and facial surgery ( 22 , 23 ), cardiac surgery ( 24 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…With additional research, nitinol was found to have distinctive properties such as unique memory of geometric shapes, superelasticity, high strength, resistance to rust, non-magnetic properties, wear resistance, and fatigue resistance ( 20 ). Due to its non-toxic resistance to human medium corrosion and good cell adhesion, nitinol is widely used in orthopedics ( 21 ), gastrointestinal and facial surgery ( 22 , 23 ), cardiac surgery ( 24 ), etc.…”
Section: Discussionmentioning
confidence: 99%